2000
DOI: 10.1034/j.1399-3003.2000.01523.x
|View full text |Cite
|
Sign up to set email alerts
|

Second messengers, ion channels and pharmacology of airway smooth muscle

Abstract: Second messengers, ion channels and pharmacology of airway smooth muscle I.P. HallSecond messengers, ion channels and pharmacology of airway smooth muscle. I.P. Hall. #ERS Journals Ltd 2000. ABSTRACT: The airway smooth muscle cell is the chief effector cell governing the control of airway calibre in the human lung. The contractile state of the airway smooth muscle cell is predominantly influenced by the balance of constrictor and relaxant stimuli. Agents such as histamine and acetylcholine cause airway smooth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
71
0
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 49 publications
0
71
0
6
Order By: Relevance
“…Hyvelin et al (22) reported that only ryr3 mRNA was expressed in human bronchial smooth muscle cells. The function of the type 3 ryanodine receptor is still poorly understood, whereas type 1 and type 2 ryanodine receptors have been clearly implicated in excitationcontraction coupling in skeletal and cardiac muscle (18). In the present study, caffeine, which depletes the SR via ryanodine activation and prevents it from refilling (52), had a small effect on the initial phase of increased [Ca 2ϩ ] i but a large effect on the sustained phase in all three types of HASM NKR-transfected cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyvelin et al (22) reported that only ryr3 mRNA was expressed in human bronchial smooth muscle cells. The function of the type 3 ryanodine receptor is still poorly understood, whereas type 1 and type 2 ryanodine receptors have been clearly implicated in excitationcontraction coupling in skeletal and cardiac muscle (18). In the present study, caffeine, which depletes the SR via ryanodine activation and prevents it from refilling (52), had a small effect on the initial phase of increased [Ca 2ϩ ] i but a large effect on the sustained phase in all three types of HASM NKR-transfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, a limitation of the interpretation of the results of the present study is that SKF-96365 also has a minor inhibitory effect on voltage-gated Ca 2ϩ channels (56). The sustained Ca 2ϩ response is important for maintaining the contractile response to agonist (18) and requires the continued presence of agonist (11,39). In the sustained phase, SOCE has been considered as the predominant source of Ca 2ϩ influx (11,35).…”
Section: Discussionmentioning
confidence: 99%
“…
(11,15,20,26,38,39,46) or by plasma membrane Ca 2ϩ influx.TNF␣, a potent proinflammatory cytokine found in bronchoalveolar lavage fluid (12) and sputum (50) from asthmatics, has been implicated as a mediator in the pathophysiology of asthma (45, 51, 52) and chronic obstructive pulmonary disease (8, 16). Indeed, TNF␣ has been shown to enhance ASM contractility (13,43,47 (11,20,46) as well as via ryanodine receptor (RyR) channels (15, 26), the latter resulting from increased levels of the novel second messenger cyclic ADP ribose (cADPR) (27,39).
…”
mentioning
confidence: 99%
“…Indeed, TNF␣ has been shown to enhance ASM contractility (13,43,47 (11,20,46) as well as via ryanodine receptor (RyR) channels (15, 26), the latter resulting from increased levels of the novel second messenger cyclic ADP ribose (cADPR) (27,39). cADPR, in turn, is synthesized and degraded by the bifunctional ectoenzyme CD38 via ADP ribosyl cyclase and cADPR hydrolase activities, respectively (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation